Programmable Bidirectional Folding of Metallic Thin Films for 3D Chiral Optical Antennas. Issue 19 (10th March 2017) - Mao, Yifei; Zheng, Yun; Li, Can; Guo, Lin; Pan, Yini; Zhu, Rui; Xu, Jun; Zhang, Weihua; Wu, Wengang
Abstract : 3D structures with characteristic lengths ranging from nanometer to micrometer scale often exhibit extraordinary optical properties, and have been becoming an extensively explored field for building new generation nanophotonic devices. Albeit a few methods have been developed for fabricating 3D optical structures, constructing 3D structures with nanometer accuracy, diversified materials, and perfect morphology is an extremely challenging task. This study presents a general 3D nanofabrication technique, the focused ion beam stress induced deformation process, which allows a programmable and accurate bidirectional folding (−70°–+90°) of various metal and dielectric thin films. Using this method, 3D helical optical antennas with different handedness, improved surface smoothness, and tunable geometries are fabricated, and the strong optical rotation effects of single helical antennas are demonstrated. Abstract : A general 3D nanofabrication technique, focused ion beam stress induced deformation process, is presented which enables programmable and accurate bidirectional folding (−70°–+90°) of various metal and dielectric thin films. Using this method, 3D helical optical antennas with different handedness, improved surface smoothness, and tunable geometries are fabricated, and the strong optical rotation effects of single helical antenna are demonstrated.